2016
DOI: 10.5098/hmt.7.10
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Flow of a Nanofluid Between Expanding or Contracting Permeable Walls With Thermal Radiation

Abstract: In the present study, the flow and heat transfer characteristics of a nanofluid in an expanding or contracting porous channel with different permeabilities in presence of thermal radiation are investigated. Analytical solutions for the flow variables are obtained by employing homotopy analysis method (HAM). Maxwell-Garnetts and Brinkman models are considered to calculate the thermal conductivity and the viscosity of nanofluid. In this investigation, we considered water and ethylene glycol as base fluids and si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…An analytical analysis was conducted by Srinivas et al [42] to examine the effects of chemical reactions on the MHD nano liquid flow with heat source/sink in a contracting/expanding porous pipe. In the presence of thermal radiation, the properties of the heat transfer flow of a nanoliquid in a porous space with varying permeabilities were examined by Vijayalakshmi and Srinivas [43]. The influence of velocity slip on the peristaltic MHD flow of a nanofluid in a porous-spaced non-uniform channel with Joule heating was examined by Sucharitha et al [44].…”
Section: Introductionmentioning
confidence: 99%
“…An analytical analysis was conducted by Srinivas et al [42] to examine the effects of chemical reactions on the MHD nano liquid flow with heat source/sink in a contracting/expanding porous pipe. In the presence of thermal radiation, the properties of the heat transfer flow of a nanoliquid in a porous space with varying permeabilities were examined by Vijayalakshmi and Srinivas [43]. The influence of velocity slip on the peristaltic MHD flow of a nanofluid in a porous-spaced non-uniform channel with Joule heating was examined by Sucharitha et al [44].…”
Section: Introductionmentioning
confidence: 99%
“…They found that with an increase in the Hartman parameter, the temperature profile declines, and the concentration of the fluid increases. In 2016, Vijayalakshmi et al 26 studied the heat transmission mechanism of the contracting or stretching parallel porous channels in response to thermal radiation. In 2017, Fakour et al 27 investigated the conduction of heat in the laminar flow of fluid between permeable walls in the presence of a magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, they dedicated toward the nanofluids analysis from multiple physical aspects. Vijayalakshmi and Srinivas 39 examined the dynamics of nanofluid inside two absorber walls with Darcy effects and thermal radiations. The authors deduced that inclusions of Darcy media controlled the working fluid movement and thermal radiations enhanced the heat transport mechanism.…”
Section: Introductionmentioning
confidence: 99%